Perawatan Diri dengan Kualitas Hidup Pasien Skizofrenia - Alvandi Poluan; I Made Rantiasa; Helly Katuuk (Lembaga Pengembangan Kinerja Dosen, 2025)
Patients with mental disorders often face a decrease in the quality of their ability to carry out daily activities and social interactions. One of the factors that can affect the quality of life of patients with mental disorders is their self-care ability. The purpose of this study was to determine the relationship between self-care ability and quality of life of schizophrenia patients at Prof. Dr. V. L. Ratumbuysang Mental Hospital. This Method of research is correlation and uses cross sectional research design. The population in this study amounted to 52 patients with schizophrenia, the sampling technique used purposive sampling technique using inclusion criteria so that the sample obtained was 32 patients. The results of this study are based on the Sperman Rho test the result of the p value is 0.000 which is smaller than the significant value (a = 0.05), then the correlation coefficient is also found to be 0.752 which can be interpreted in the strong relationship category, thus it can be said that in this study H0 is rejected and Ha is accepted which means that there is a relationship between self-care skills and the quality of life of schizophrenic patients at Prof. Dr. V. L. Ratumbuysang Mental Hospital. The conclusion of this study is a significant relationship between the role of nurses and the implementation of self-care in schizophrenic patients, the better the self-care skills, the better the quality of life in patients with schizophrenic mental disorders Guidance and coaching provided by nurses can help patients develop better self-care skills